DEVELOPING CHILDREN GROSS MOTOR SKILLS THROUGH COMBINATION OF EXPLICIT INSTRUCTION MODEL, ROLE PLAYING MODEL AND JUMP ROPE GAME IN KINDERGARTEN - Wahyudi, Mohammad Dani; Sin, Ishak; Fauzana, Eka (Journal of K6, Education and Management, 2018)
The main purpose of this research is to develop children gross motor skill in performing physical game regularly. This research applied qualitative approach with classroom action research type that conducted on group B Aisyiyah Kindergarten 31 of Banjarmasin explicit instruction model, role playing model and jump rope game. The result of the research shows teacher?s activities? improvement affecting the children improvement skills in gross motor development.